2011
DOI: 10.1007/s12015-011-9250-x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Parameters Involved in the Establishment of New Lines of Human Embryonic Stem Cells

Abstract: Since the derivation of the first human embryonic stem cell (hESC) lines by Thomson and coworkers in 1998, more than 1,200 different hESC lines have been established worldwide. Nevertheless, there is still a recognized interest in the establishment of new lines of hESC, particularly from HLA types and ethnic groups currently underrepresented among the available lines. The methodology of hESC derivation has evolved significantly since 1998, when human LIF (hLIF) was used for maintenance of pluripotency. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
2
19
0
2
Order By: Relevance
“…LIF is one of the genes expressed in unrestricted somatic stem cells, which have been described as recapitulating the characteristics of mesenchymal stem cells (MSCs) from placental cord blood and, among the recently proposed transcriptome-based subtypes of MSCs [23], are therefore the most closely related to human embryonic stem cells (hESCs). Accordingly, LIF (alone or in combination with bFGF), is the main factor maintaining the pluripotency of hESCs during derivation and long-term culture [36]. It has more recently been demonstrated that LIF induces the expression of miRNA-21, a miRNA that promotes EMT through STAT3 signalling in human tumor cells [19] and was shown in our ISH experiments to be expressed at similar levels in all three classes.…”
Section: Discussionmentioning
confidence: 62%
“…LIF is one of the genes expressed in unrestricted somatic stem cells, which have been described as recapitulating the characteristics of mesenchymal stem cells (MSCs) from placental cord blood and, among the recently proposed transcriptome-based subtypes of MSCs [23], are therefore the most closely related to human embryonic stem cells (hESCs). Accordingly, LIF (alone or in combination with bFGF), is the main factor maintaining the pluripotency of hESCs during derivation and long-term culture [36]. It has more recently been demonstrated that LIF induces the expression of miRNA-21, a miRNA that promotes EMT through STAT3 signalling in human tumor cells [19] and was shown in our ISH experiments to be expressed at similar levels in all three classes.…”
Section: Discussionmentioning
confidence: 62%
“…7 To date, more than 1000 hES cell lines have been derived in laboratories worldwide, and rapid advances in the knowledge and technologies associated with the culture conditions of hES cells have made it possible to derive new hES cell lines under clinical or near clinical conditions for further use. 8 Although the embryos may display poor morphology, they remain a major source of starting material for the isolation of hES cells, and several methods have been applied to improve the success of hES cell derivation. Culturing poor-quality embryos in a modified culture medium increased blastocyst formation, 9 and using mesenchymal stem cells as feeder cells also facilitated the derivation of hES cells from poor-quality embryos.…”
Section: Introductionmentioning
confidence: 99%
“…The first in-man transfusion is likely to be from one of these two cell sources with studies of red cells generated from hESC or hiPSC coming later [170172]. Currently 1200 hESC lines have been established worldwide, and 375 of these are deposited in two international registries [172].…”
Section: Resultsmentioning
confidence: 99%
“…Currently 1200 hESC lines have been established worldwide, and 375 of these are deposited in two international registries [172]. Investigators at the forefront of ex vivo expansion studies expect that GMP compliant facilities to produce red cells ex vivo will be available within the next 2-3 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation